Clean Water Self-Sufficiency and Well Water Filtration Method Education for Health Workers in Gowa Regency - Andayanie, Ella; Baharuddin, Alfina; Harma, Asmarani; Junaid, Annisa; Yuliati, Yuliati; A. Fachrin, Suharni (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2025)
The quality of well water in Jenemadingi hamlet does not meet health standards. As a result, cases of diarrhea and stunting are also high. The purpose of this community service is to provide training in water purification techniques. This educational method is carried out in five stages, namely: the socialization stage and the implementation stage. This activity includes three sessions, namely: the first stage: pre-test, which is administered through a questionnaire, using lecture, question-and-answer, and discussion methods; post-test and evaluation of post-test results; technology implementation stage; monitoring and evaluation stage; and program sustainability stage. The results of the community service activity indicate that the socialization of clean water and sanitation education is beneficial for the community, as the community's knowledge has significantly improved. The average score increased from 20.22 in the pre-test to 23.18 in the post-test, with a p-value of 0.001, indicating a significant difference. These results confirm the effectiveness of the clean water sanitation education program.